Impact of reservoir heterogeneity on oil migration and the origin of oil-water contacts: McMurray Formation type section, Alberta, Canada. (May 2019) - Fustic, Milovan; Strobl, Rudy; Fowler, Martin; Jablonski, Bryce V.; Martinius, Allard W.
Abstract: This study documents and attempts to describe the processes leading to the formation and preservation of exposed oil, water, and paleo-gas contacts at the McMurray Formation type section, Alberta, Canada. The McMurray Formation type section, a part of the Athabasca Oil Sands Deposit (AOSD), the largest exhumed oil reservoir on Earth, is unparralled, still underutilized, natural laboratory for veryfing and refining existing, and developing new concepts, for oil migration and post oil-emplacement fluid diffusion and biodegradation processes in a sedimentologically complex reservoir setting. Exposures, coupled with adjacent borehole data, provide a three-dimensional insight into reservoir heterogeneities and their influence on oil migration, entrapment, post-emplacement fluid mixing, and biodegradation processes and products, in a hierarchical and chronological order from early charge to present-day conditions. The principles of oil above water and of horizontal or tilted oil/water contacts are challenged by outstanding examples of: (i) centimetre to decimetre scale inter-fingering oil-water stringers/contacts, created by capillary pressure differences and partial charge; (ii) irregular oil-water contacts in both clean and heterogeneous reservoirs characterized by gravitational effects caused by severe biodegradation that caused the formation of extra heavy-oil commonly referred to as "bitumen" that sank through the water column; (iii) occurrences of multiple metre-scale intervals with less than 50% oil saturation, commonly referred to as lean zones that formed during microbial gas generation following oil entrapment. Studied contacts provided excellent opportunity to study oil migration and charging mechanisms from pore and sedimentary bed to reservoir scale at various stages of oil migration into the reservoir, as well as oil, water, and gas re-migration within the reservoir (trap). Described exposures can play an additional role in advancing geoscience education, petroleum exploration, reservoir characterization, field development, and production optimization studies. Highlights: This study documents exposed oil, water, and paleo-gas contacts. It is novel and unique in terms that petroleum reservoirs are rarely exhumed. Study includes outcrop observations, and geochemical data from a drillhole from behind the outcrop. Results challenge the principles of oil above water and of horizontal or tilted oil/water contacts in heavy oil reservoirs.